Inhibitory Effects of Columbianadin on Nociceptive Behaviors in a Neuropathic Pain Model, and on Voltage-Gated Calcium Currents in Dorsal Root Ganglion Neurons in Mice - Su, Xiaolin; Wu, Bin; Zhang, Wentong; Ji, Yong-Hua; Wang, Qiuhong; Tan, Zhi-Yong (Frontiers in Pharmacology, 2020)
Radix angelicae pubescentis (RAP) has been used in Chinese traditional medicine to treat painful diseases such as rheumatism and headache. A previous study has reported that columbianadin (CBN), a major coumarin in RAP inhibits acute and inflammatory pain behaviors. However, the effects of CBN on neuropathic pain behaviors, and the potential underlying mechanism have not been reported. In the present study, the effects of CBN, compared to another major coumarin of RAP osthole (OST), on oxaliplatin-induced neuropathic pain behaviors and on the voltage-gated calcium currents in small dorsal root ganglion (DRG) neurons were studied in mice. It was found that CBN and OST inhibited both mechanical and cold hypersensitivity induced by oxaliplatin. Moreover, CBN and OST might preferentially inhibit T- and L-type calcium currents (Ica). The inhibitory effects of CBN and OST on the oxaliplatin-induced mechanical allodynia were prevented by gabapentin. These results suggest that CBN, as well as OST might inhibit neuropathic pain behaviors through an inhibition of T- and L-type calcium currents in nociceptive DRG neurons.